The extent of price variation amongst branded antihypertensive drugs and its association with number of pharmaceutical companies - Kumar, Rahul; Manu, Chandrama; Singh, Dheeraj Kumar; Lakhani, Preet; Tutu, Sachin; Dixit, Rakesh Kumar (International Journal of Research in Medical Sciences, 2017)
Background: The study was performed to analyze the extent of price variation amongst branded antihypertensive drugs in India and the relation of this price variation to number of pharmaceutical companies manufacturing/marketing these drugs. Methods: Price of different brands of antihypertensive drugs was collected from authentic sources. The data were segregated and the percentage price variation was calculated applying suitable statistical tools. Results: A total of 116 formulations from different companies representing 38 antihypertensive drugs were analyzed. Maximum price variation (3233.33%) was seen with 10 mg dose of propranolol. In general the price variations are proportionally correlated to the number of pharmaceutical companies. Conclusions: Price variation of great extent was found among many formulations. Physicians should be aware of these variations for choosing the appropriate brand for rational therapeutics. This will reduce the burden on patients and family.